The mechanism of Tyk2 deficiency-induced immunosuppression in mice involves robust IL-10 production in macrophages. (June 2020) - Hirashima, Koki; Muromoto, Ryuta; Minoguchi, Hiroya; Matsumoto, Tomohiro; Kitai, Yuichi; Kashiwakura, Jun-ichi; Shimoda, Kazuya; Oritani, Kenji; Matsuda, Tadashi
Highlights: Heat-killed P. acnes -induced peritonitis was reduced in Tyk2 KO mice independently of IFNs. Tyk2 KO macrophages produced a greater amount of IL-10 than WT macrophages. The enhanced IL-10 production was correlated to an enhanced activation of PGE2 -PKA signaling. These data provide an additional explanation for the immunosuppression seen in Tyk2 KO mice. Abstract: Macrophages are highly plastic in their pro-inflammatory/anti-inflammatory roles. Type I and II interferons (IFNs) are known to modulate macrophage activation. Tyrosine kinase 2 (Tyk2) has an intimate relationship with type I and II IFN signaling. Animal studies have shown that Tyk2 knock-out (KO) in mice is associated with reduced inflammatory responses in various mouse models of diseases. To investigate the role of Tyk2 in inflammation in more detail, we intraperitoneally injected heat-killed Propionibacterium acnes ( P. acnes ) to Tyk2 KO mice. P. acnes –induced acute peritoneal inflammation, assessed by neutrophil infiltration, was reduced in Tyk2 KO mice. The reduction was accompanied with diminished productions of inflammatory cytokines and an enhanced production of anti-inflammatory IL-10. Unexpectedly, pre-treatment of wild-type mice with the neutralizing antibodies for IFNs did not affect P. acnes -induced neutrophil infiltration. A neutralizing antibody for the IL-10 receptor in Tyk2 KO mice restored P. acnes -induced peritoneal inflammation. Enhanced production of IL-10 from Tyk2 KO peritoneal cells was suppressed by either the cyclooxygenase inhibitor diclofenac or protein kinase A inhibitor H-89. The level of prostaglandin E2 (PGE2 ) in the steady-state peritoneal cavity in Tyk2 KO mice was higher than that in wild-type mice. Tyk2 KO macrophages showed an enhanced CREB phosphorylation induced by P. acnes plus PGE2 . Taken together, these results showed that Tyk2 deficiency potentiates the PGE2 -protein kinase A-IL-10 pathway in macrophages, and thereby contributes to potentiation of the immunosuppressive phenotype.